Understanding Ipv6 - Davies, Joseph (Microsoft Press, 2011)
nternet Protocol version 6 (IPv6) greatly improves on IPv4 by vastly increasing the number of available addresses and by enabling more efficient routing, simpler configuration, built-in IP security, better support for real-time data delivery, and other essential enhancements. Find out all about this next-generation IP—from its features and benefits to its packet structure and protocol processes—in UNDERSTANDING IPV6. This book-plus-CD package thoroughly discusses IPv6 protocols and processes and describes how IPv6 is supported in the latest versions of the Microsoft® Windows® operating system, including the upcoming Windows Server 2003 family. It also describes transition technologies that allow you to deploy IPv6 in IPv4 intranets and across the IPv4 Internet. It’s ideal for any network administrator, consultant, engineer, technician, or student who wants to understand the importance of IPv6 and how it works and begin planning to transition to IPv6 internetworking.